A taxonomic review of Korean Liogluta Thomson (Coleoptera, Staphylinidae, Aleocharinae) with descriptions of three new species - Lee, Seung-Gyu; Ahn, Kee-Jeong (Zootaxa, 2016)
A taxonomic review of the Liogluta Thomson in Korea is presented. The genus is represented in Korea by eight species including three new species, L. changwhani Lee & Ahn, sp. nov., L. jinilli Lee & Ahn, sp. nov. and L. rufescens Lee & Ahn, sp. nov. Two species [L. distans (Sharp) and L. ursi (Sawada)] are new to the Korean peninsula and L. pyonganica is recorded for the first time in South Korea. A key, descriptions, habitus photographs and illustrations of the diagnostic characters are provided.